Crustal volatile release at Merapi volcano; the 2006 earthquake and eruption events. (17th May 2013) - Troll, Valentin R.; Chadwick, Jane P.; Jolis, Ester M.; Deegan, Frances M.; Hilton, David R.; Schwarzkopf, Lothar M.; Blythe, Lara S.; Zimmer, Martin
<x xml:space="preserve">Abstract</x> High‐temperature gas in volcanic island arcs is widely considered to originate predominantly from the mantle wedge and from subducted sediments of the down‐going slab. Over the decade (1994–2005) prior to the 2006 eruption of Merapi volcano, summit fumarole CO2 gas δ13C ratios are relatively constant at −4.1 ± 0.3‰. In contrast, CO2 samples taken during the 2006 eruption and after the May 26th 2006 Yogyakarta earthquake (M6.4) show a dramatic increase in carbon isotope ratios to −2.4 ± 0.2‰. Directly following the earthquake (hypocentre depth 10–15 km), a 3–5‐fold increase in eruptive intensity was observed. The elevated carbon isotope gas data and the mid‐crustal depth of the earthquake source are consistent with crustal volatile components having been added during the 2006 events, most probably by the thick local limestone basement beneath Merapi. This 'extra' crustal gas likely played an important role in modifying the 2006 eruptive behaviour at Merapi and it appears that crustal volatiles are able to intensify and maintain eruptions independently of traditional magmatic recharge and fractionation processes.